Rates and pathways of iodine speciation transformations at the Bermuda Atlantic Time Series - Schnur, Alexi A.; Sutherland, Kevin M.; Hansel, Colleen M.; Hardisty, Dalton S. (Frontiers in Marine Science, 2024)
The distribution of iodine in the surface ocean – of which iodide-iodine is a large destructor of tropospheric ozone (O3) – can be attributed to both in situ (i.e., biological) and ex situ (i.e., mixing) drivers. Currently, uncertainty regarding the rates and mechanisms of iodide (I-) oxidation render it difficult to distinguish the importance of in situ reactions vs ex situ mixing in driving iodine’s distribution, thus leading to uncertainty in climatological ozone atmospheric models. It has been hypothesized that reactive oxygen species (ROS), such as superoxide (O2•−) or hydrogen peroxide (H2O2), may be needed for I- oxidation to occur at the sea surface, but this has yet to be demonstrated in natural marine waters. To test the role of ROS in iodine redox transformations, shipboard isotope tracer incubations were conducted as part of the Bermuda Atlantic Time Series (BATS) in the Sargasso Sea in September of 2018. Incubation trials evaluated the effects of ROS (O2•−, H2O2) on iodine redox transformations over time and at euphotic and sub-photic depths. Rates of I- oxidation were assessed using a 129I- tracer (t1/2 15.7 Myr) added to all incubations, and 129I/127I ratios of individual iodine species (I-, IO3-). Our results show a lack of I- oxidation to IO3- within the resolution of our tracer approach – i.e., <2.99 nM/day, or <1091.4 nM/yr. In addition, we present new ROS data from BATS and compare our iodine speciation profiles to that from two previous studies conducted at BATS, which demonstrate long-term iodine stability. These results indicate that ex situ processes, such as vertical mixing, may play an important role in broader iodine species’ distribution in this and similar regions.